Use of e-cigarettes and associated factors among adolescent smokers in Indonesia: Analysis of the Global Youth Tobacco Survey (GYTS) Indonesia 2019 - Marice Marice; Henny Kaseger; Yunida Hariyanti; Wahyuni Hafid; Niluh Desy Purnamasari; I Wayan Supetran; Hairil Akbar; Maretalinia Maretalinia (Public Health of Indonesia)
Background: Electronic cigarette (e-cigarette) is an alternative to reduce the harmfulness of conventional cigarettes. However, there are still pros and cons to using the e-cigarette, especially among adolescents. Instead of reducing the health problem, using e-cigarette even make the illness the same as conventional ones.